Health behaviours and outcomes associated with fly-in fly-out and shift workers in Western Australia - Joyce, S.; Tomlin, S.; Somerford, Peter; Weeramanthri, T. (2013)
Aims: To examine the association of health behaviours and outcomes with employment type in the West Australian adult population. Methods: Cross-sectional study of employed adults aged 16years and over using self-reported information collected in the WA Health and Wellbeing Surveillance System between 2008 and 2010. A total of 380 fly-in fly-out (FIFO) workers, 913 shift workers and 10613 workers of other employment types were identified. Results: FIFO workers exhibited similar health behaviours to shift workers but had a different sociodemographic profile. Compared with other employment types, FIFO workers were significantly more likely to be current smokers, drink alcohol at risky levels, and be overweight or obese, after adjusting for age, sex and survey sampling strategies. They were less likely to report current mental health problems. Conclusions: Self-reported health behaviours of FIFO workers differ from other employment types. FIFO workers are expected to increase in number over the next decade, as the mining and resources sector expands in Australia. Our findings suggest that health interventions, whether in the workplace or clinical settings, need to be informed by the demographic mix of the cohort of workers on entry as they are not a homogenous group, and targeted towards specific employment patterns (length of shifts and type of employment) to improve their current and future well-being. © 2012 Royal Australasian College of Physicians.